On optimal and suboptimal treatment strategies for a mathematical model of leukemia - Elena Fimmel; Yury S. Semenov; Alexander S. Bratus (Mathematical Biosciences and Engineering)
In this work an optimization problem for a leukemia treatment modelbased on the Gompertzian law of cell growth is considered. The quantitiesof the leukemic and of the healthy cells at the end of the therapy are chosenas the criterion of the treatment quality. In the case where the number ofhealthy cells at the end of the therapy is higher than a chosen desired number,an analytical solution of the optimization problem for a wide class of therapyprocesses is given. If this is not the case, a control strategy called alternative issuggested.